PENDETEKSIAN KETIDAKWAJARAN SEKOR BERDASARKAN METODE JACOB DITINJAU DARI JUMLAH PILIHAN JAWABAN PADA TES PILIHAN GANDA - Awwalunnisa, Mugia Rahayu (2014)
This research was conducted in The State Vocational School no.1 (SMKN 1) Bandung, The State Vocational School no.3 (SMKN 3) Bandung and The State Vocational no.11 (SMKN 11) Bandung. The research objective was to find out whether the inappropriateness score object index in three options and five options have different proportion in multiple-choice test or not. It is a descriptive research that used amodel of appropriateness index comparison. In this research, population was first grade students of Accounting Class in State Vocational Schools. Moreover, the analysis of different item discrimination technique and difficulty level resulted in medium item discrimination both in 3 and 5 multipleanswers questions. Jaccob Method used to the calculation of inappropriateness index. The calculation results showed that 8 of the respondents who answered the 3 multiple answers questions have inappropriate scores, and 1 of the respondents who answered 5-answer choices questions had inappropriate scores. Based on the statistical analisis, the description of score inappropriateness seen from the numbers of answer choices are: (1) low achiever respondents to get appropriate score was bigger when they are provided with 5 multiple answers; and (2) high achiever students to get appropriate score was possible both with 5 and 3 multiple answers.